Lipoma in Parotid Gland: A Rare Case Report - Santoso, Sergio; Rizqiawan, Andra; Mulyawan, Indra; Wihandono, Asdi; Amir, Muhammad Subhan (European Journal of Dentistry, 2023)
Lipoma is a benign, rare, mesenchymal tumor found in the head and neck region, especially in the parotid gland. It thus requires a careful and precise examination to establish a diagnosis. A surgical procedure of the parotid gland is challenging due to the associated risk factor of facial nerve injury. We report a rare case of head and neck region lipoma between the superficial and deep lobe of the parotid gland. A 44-year-old female patient was presented with the chief complaint of a painless lump on the left front ear to the left cheek for about 1 year. There were no complaints of tooth pain before the lump appeared, and there were no lumps in other regions. A fine-needle aspiration biopsy, ultrasonography, and magnetic resonance imaging were all performed to establish the preoperative diagnosis and to plan the correct surgical approach. Lipoma was the initial clinical diagnosis, and a surgical excision with superficial parotidectomy and facialis nerve preservation was performed. Follow-up examinations were conducted to assess any facial nerve injury complications. Conclusion Lipoma rarely grows in the parotid gland. Careful diagnosis should be performed to establish a precise surgery for parotid dissection and facial nerve preservation.
Keywords: lipoma; parotid gland; parotidectomy; medicine; dentistry